Prenatal Alcohol Exposure is Associated with Regionally Thinner Cortex During the Preadolescent Period - Robertson, Frances C. (Cereb Cortex, 2016)
Children with fetal alcohol spectrum disorders (FASD) may exhibit craniofacial dysmorphology, neurobehavioral deficits, and reduced brain volume. Studies of cortical thickness in FASD have yielded contradictory findings, with 3 reporting thicker cerebral cortex in frontal and temporal brain regions and 2 showing thinner cortex across multiple regions. All 5 studies included subjects spanning a broad age range, and none have examined continuous measures of prenatal alcohol exposure. We investigated the relation of extent of in utero alcohol exposure to cortical thickness in 78 preadolescent children with FASD and controls within a narrow age range. A whole-brain analysis using FreeSurfer revealed no significant clusters where cortical thickness differed by FASD diagnostic group. However, alcohol dose/occasion during pregnancy was inversely related to cortical thickness in 3 regions—right cuneus/pericalcarine/superior parietal lobe, fusiform/lingual gyrus, and supramarginal/postcentral gyrus. The effect of prenatal alcohol exposure on IQ was mediated by cortical thickness in the right occipitotemporal region. It is noteworthy that a continuous measure of maternal alcohol consumption during pregnancy was more sensitive than FASD diagnosis and that the effect on cortical thickness was most evident in relation to a measure of maternal binge drinking.